Yielding behavior of triplex medium Mn steel alternated with cooling strategies altering martensite/ferrite interfacial feature. (1st November 2022) - Hu, Bin; Shen, Xiao; Guo, Qinyi; Wen, Qinghua; Tu, Xin; Ding, Cancan; Ding, Fanglin; Song, Wenwen; Luo, Haiwen
Highlights: Solute segregation at various interfaces characterized atomically in triplex medium Mn steel. Two cooling strategies produced different martensite/ferrite interfaces for distinct yielding behavior. Density and mobile ability of dislocations near martensite/ferrite interfaces determine yielding behavior. Abstract: In this paper, we report the influence of cooling processes on the yielding behavior of a medium Mn steel (MMS) with triplex microstructure, i.e. austenite (γ), ferrite (α) and as-quenched martensite (α'). After the intercritical annealing (IA) at both 725 ℃ and 750 ℃, the steel was subjected to the two cooling processes, i.e. air cooling (AC) and water quenching (WQ). It exhibits the discontinuous yielding after the AC following the IA at 750 ℃ while the continuous yielding after the WQ. Compared with WQ process, both the dilatometry and the microstructural examinations show that the AC process leads to lower M s temperature, larger retained austenite (RA) fraction and less martensite, the latter is always companied with geometry necessary dislocations (GNDs) generated near the α/α' interfaces. Considering the complexity of nanosized tri-phases in this steel, the presence of martensite with key features in the resultant specimens was systematically examined by atom probe tomography (APT) on the samples prepared by the specific target lift-out method. The APT results directly revealed the C/Mn co-segregation at the α'/α interfaces in the AC samples but not in WQ samples. The numerical simulation results further suggest that the segregation of C and Mn at the α'/α interfaces may be due to different mechanisms. We conclude that the yielding of triplex MMS is determined by both the quantity of GNDs generated near the α/α' interfaces, which increases with martensite fraction, and the extent of their immobilization resulting from the interfacial segregation of solute atoms when the presence of martensite is sufficient. WQ tends to suppress the discontinuous yielding of MMS since the rapid cooling may promote more martensite formed with the increasing quantity of GNDs and prevent the interfacial segregation of both C and Mn.